ADMI: A Multi-Agent Architecture To Autonomously Generate Data Mining Servrces. - Hassan Zaid, Syed Zahid; Abidi, S. S. R.; Manikam, S.; Cheah, Yu-N (2004)

(untitled)
This paper presents a case for an intelligent agent based framework for knowledge discovery in a distributed environment comprising multiple heterogeneous data repositories.